Phylogenomic Classification and Biosynthetic Potential of the Fossil Fuel-Biodesulfurizing Rhodococcus Strain IGTS8 - Thompson, Dean; Cognat, Valérie; Goodfellow, Michael; Koechler, Sandrine; Heintz, Dimitri; Carapito, Christine; Van Dorsselaer, Alain; Mahmoud, Huda; Sangal, Vartul; Ismail, Wael (Frontiers in Microbiology, 2020)
Rhodococcus strain IGTS8 is the most extensively studied model bacterium for biodesulfurization of fossil fuels via the non–destructive sulfur–specific 4S pathway. However, the taxonomic status of this strain, which was initially assigned to the species Rhodococcus rhodochrous and later to Rhodococcus erythropolis, is controversial. Phylogenomic analyses of the whole genome of strain IGTS8 and closely related rhodococci showed that R. erythropolis and Rhodococcus qingshengii are very closely related species, that Rhodococcus strain IGTS8 is a R. qingshengii strain and that several strains identified as R. erythropolis should be re-classified as R. qingshengii. The genomes of strains assigned to each of these species contain potentially novel biosynthetic gene clusters showing that these species should be given greater importance in discovery of new antimicrobials and other industrially important biomolecules. The plasmid-born dsz operon encoding fossil fuel desulfurization enzymes was not only present in R. qingshengii IGTS8 but also in R. erythropolis XP, suggesting that it might be easily transferred between members of these species.